Rancang Bangun Aplikasi Point of Sale dengan Menggunakan QR Code pada PT. Akari Berbasis Android - Sura, Ranji Adi; Muhammad Fauzi (Universitas Methodist Indonesia, 2025)
The development of information technology encourages companies to improve the efficiency and effectiveness of business operations, including in the sales transaction process. PT. Akari requires a system that can simplify transaction management and sales recording and minimize errors. This study designs and builds an Android-based Point of Sale (POS) application that utilizes QR Code technology as a product identification medium. This POS application has a main feature in the form of QR code scanning to accelerate the process of product data input, sales data management, stock recording, and automatic report preparation. Test results indicate that all functions in the application can operate properly on Android devices and are able to increase transaction speed and sales recording accuracy. With this application, PT. Akari obtains a more modern and efficient sales system that supports the digitalization of business processes.